2014
DOI: 10.1016/j.juro.2014.03.096
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Resident Involvement on Urological Surgery Outcomes: An Analysis of 40,000 Patients from the ACS NSQIP Database

Abstract: Urology resident involvement is not associated with increased overall and surgical complications. It may even be protective when adjusted for appropriate factors such as case mix, complexity and operative time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 27 publications
6
49
0
Order By: Relevance
“…Others have demonstrated that inclusion of residents in surgical cases increased operative time compared to attending physicians performing the procedure alone. [10][11][12][13] The effect of the duty hour restrictions on patient outcomes in the surgical literature is conflicting. [14][15][16] Studies in general surgery and obgyn suggest that laboratory-based training leads to more rapid improvement in technical skills and that residents who participate in laboratory-based/simulation training achieve greater competency during patient procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that inclusion of residents in surgical cases increased operative time compared to attending physicians performing the procedure alone. [10][11][12][13] The effect of the duty hour restrictions on patient outcomes in the surgical literature is conflicting. [14][15][16] Studies in general surgery and obgyn suggest that laboratory-based training leads to more rapid improvement in technical skills and that residents who participate in laboratory-based/simulation training achieve greater competency during patient procedures.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Although operative time was not available for analysis, urologic procedures with resident involvement have been shown to have longer operative times but lower overall complication rates. 18 In addition, teaching hospitals tend to be highervolume facilities, which is also associated with lower rates of surgical complications. 19,20 This may also contribute to the finding that teaching hospital status was not an independent risk factor for RM.…”
Section: Commentmentioning
confidence: 99%
“…3,4 Numerous studies were conducted to elucidate the relationship between resident involvement and postoperative complications with conflicting results. [5][6][7][8][9][10][11][12] Several studies have demonstrated that resident involvement was not a risk factor for increased complications in neurosurgery, orthopedic surgery, or urology. [5][6][7][8] Meanwhile, other studies have shown increased operative durations and post-operative complications when residents were involved in surgery.…”
mentioning
confidence: 99%